En bloc resection of total thyroid and bilateral central compartment lymph nodes via a gasless transoral approach in papillary thyroid carcinoma - Sheng, Xuren; Liu, Jianjun; Fang, Jing; Zheng, Xucai; Wang, Shengying (Frontiers in Endocrinology, 2023)
Abstract Objective: This study aimed to summarize and explore the efficacy and safety of en bloc resection of total thyroid and bilateral central compartment lymph nodes via a gasless transoral approach in patients with papillary thyroid carcinoma. Methods: This study was conducted between January 2021 and December 2021. It involved 30 patients with bilateral papillary thyroid carcinoma who had undergone en bloc resection of the total thyroid and bilateral central compartment lymph nodes via a gasless transoral approach using a three-trocar and four-instrument technique at The First Affiliated Hospital of the University of Science and Technology of China. The key steps and difficulties of the operation were summarized, and the clinicopathological characteristics and surgical complications of patients were analyzed. Results: All operations were successful without conversion to open surgery. The pathological diagnosis was bilateral papillary thyroid carcinoma. The mean maximum tumor diameter was 0.85±0.51 cm (range 0.3–2.5 cm). There was no case of gross capsular invasion. The mean number of harvested central compartment lymph nodes was 11.36±5.36. Central compartment lymph node metastases were found in 16 patients (53.3%) with a mean of 1.53 ± 2.39. On the other hand, lymphocytic thyroiditis was observed in 12 cases (40%), and microscopic capsular invasion was observed in five cases (16.6%). All patients had normal parathyroid hormone levels after the operation. However, one patient developed hoarseness after the operation due to injury of the recurrent laryngeal nerve branch, but there was no numbness of the mandible and lower lip or infection of the oral incision. Conclusion: The study revealed that the three-trocar and four-instrument technique can be used in the en bloc resection of total thyroid and bilateral central compartment lymph nodes via a gasless transoral approach without disconnecting the thyroid isthmus. As a result, the operation is considered effective and safe. Therefore, this technique may be a better surgical method for patients with bilateral thyroid cancer and cosmetic needs.